BERMAIN SEBAGAI KEBUTUHAN DAN STRATEGI PENGEMBANGAN DIRI ANAK - Anita Yus (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
Playing games is a part of the children’s life. In playing games the children are exploring and understanding their world. This article discusses how playing games can be used in children’s education. The children can play anywhere and anytime they want. The context, place, and time will determine the forms, activities, and game content. In playing games, the children plan, concentrate on doing certain tasks, solve problems, and express their ideas. This article concludes that playing games can be designed and used as a strategy of the children self development. Learning activities to be done by the children are integrated in playing activities. These activities facilitate the children to gain new knowledge and experience.